Performance of Continuous Hydrogen Production from Perhydro Benzyltoluene by Catalytic Distillation and Heat Integration Concepts with a Fuel Cell - Rüde, Timo; Lu, Yanye; Anschuetz, Leon; Blasius, Marco; Wolf, Moritz; Preuster, Patrick; Wasserscheid, Peter; Geißelbrecht, Michael (Energy Technology, 2023)
The benzyltoluene-based liquid organic hydrogen carrier (LOHC) system enables the safe transport and loss-free storage of hydrogen. At least 26% of the lower heating value of the released hydrogen, however, has to be invested in form of heat to release the stored hydrogen. The low operation temperatures of catalytic distillation (CD) can facilitate waste heat integration to reduce external heat demand. Herein, the continuous hydrogen release from perhydro benzyltoluene via CD is demonstrated. It is revealed in the experimental results that this mode of operation leads to a high hydrogen release rate and very efficient noble metal catalyst usage at exceptionally mild conditions. The hydrogen-based productivity of platinum of 0.35 g(H2) g(Pt)(-1) min(-1) (0.7 kW(LHV_H2) g(Pt)(-1)) at a dehydrogenation temperature of only 267 degrees C is found to be nearly four times higher than for the conventional continuous liquid-phase dehydrogenation at the same temperature. Furthermore, simulation results of the CD process are described. The feasibility of a fully heat-integrated process for electricity generation from the released hydrogen via CD using waste heat from the fuel cell for the CD reboiler is demonstrated. The technical potential of coupling the H12-BT dehydrogenation by CD with high-temperature fuel cell operation is highlighted by the simulation.
CRIS-Team WoS Importer:2023-02-24